GNAS mutation is an unusual cause of primary adrenal insufficiency: a case report - Yajie Tong; Dongmei Yue; Ying Xin; Dan Zhang (BMC, 2022)
Abstract Background Primary adrenal insufficiency in children has non-specific and extensive clinical features, so the diagnosis of its etiology is complex and challenging. Although congenital adrenal hyperplasia is the most common cause, more and more other genetic causes have been identified. GNAS mutation is easily overlooked as a rare cause of primary adrenal insufficiency. Here we firstly report a neonatal case of primary adrenal insufficiency caused by GNAS mutation. Case presentation A boy was diagnosed with congenital hypothyroidism 10 days post-partum and treated immediately. He also had persistent hyperkalaemia and hyponatraemia with elevated adrenocorticotropic hormone. At 70 days after birth, he was transferred to our hospital on suspicion of congenital adrenal hyperplasia. Physical examination found no other abnormalities except for growth retardation. Laboratory examination revealed increased aldosterone and normal cortisol, 17-hydroxyprogesterone, and androstenedione levels. Abnormally elevated parathyroid hormone was accompanied by normal blood calcium. Genetic assessment found a de novo, heterozygous c.432 + 1G > A variant in GNAS. Conclusions We report this case to highlight that GNAS mutation is an unusual cause of primary adrenal insufficiency. The combination of primary hypothyroidism and /or pseudohypoparathyroidism will provide diagnostic clues to this condition.